2010
DOI: 10.1007/s12630-010-9338-9
|View full text |Cite
|
Sign up to set email alerts
|

Emergence agitation in adults: risk factors in 2,000 patients

Abstract: Purpose The study was designed to determine the incidence of postoperative agitation following general anesthesia in 2,000 adult patients and to examine the associated risk factors. Methods The study enrolled 2,000 adults who were scheduled for surgery under general anesthesia in a single institution during December 2007 to December 2008. The following risk factors were examined: age, gender, ASA physical status, type of surgery, anesthesia technique (inhalational or intravenous), administration of neostigmine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
261
14
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(295 citation statements)
references
References 22 publications
16
261
14
4
Order By: Relevance
“…This is considered to be related to the reduction in occurrence of emergence agitation. Some studies have suggested that postoperative pain can be a risk factor related to emergence agitation (Yu et al, 2010), and there are also numerous reports suggesting that there is no relationship between pain control and emergence agitation (Zhao et al, 2012). Our study confirmed the latter, as there was no correlation between the patient's NRS score and AFPS score and no significant difference in the amount of fentanyl administered between the 2 groups.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This is considered to be related to the reduction in occurrence of emergence agitation. Some studies have suggested that postoperative pain can be a risk factor related to emergence agitation (Yu et al, 2010), and there are also numerous reports suggesting that there is no relationship between pain control and emergence agitation (Zhao et al, 2012). Our study confirmed the latter, as there was no correlation between the patient's NRS score and AFPS score and no significant difference in the amount of fentanyl administered between the 2 groups.…”
Section: Discussionsupporting
confidence: 83%
“…Yu et al (2010) reported 21.3% and Radtke et al (2010), 5%, whereas in our study, it was 20%. The difference in incidence of emergence agitation according to investigator is considered to be due to differences in criteria or differences in the standards used to define emergence agitation, where AFPS, Riker Sedation-Agitation Scale, Richmond Agitation-Sedation Scale, or personally categorized criteria have been used.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Their study results indicate that [ 20% of adult subjects experienced postanesthetic agitation. 3 Delirium, POCD, agitation-the variety of cognitive disorders studied in the perioperative period can be…well…rather confusing. Often the terms are defined poorly and sometimes they are used interchangeably.…”
mentioning
confidence: 99%
“…They then graded agitation according to the following scheme: a) mild: in response to stimulation; b) moderate: occurring without stimulation and lasting for at least five minutes but not requiring intervention; and, c) severe: lasting for at least five minutes and requiring drugs and/or physical restraint. 3 Using this definition, Yu found that 212 of 2,000 adult subjects (10.6%) experienced mild agitation, 178 (8.9%) experienced moderate agitation, and 36 (1.8%) experienced severe agitation. The frequency of agitation noted in the present study was fourfold greater than previous research in adults.…”
mentioning
confidence: 99%